Trends in Frailty Between 1990 and 2020 in Sweden Among 75-, 85-, and 95-Year-Old Women and Men: A Nationwide Study from Sweden. Issue 2 (3rd October 2022) - Wennberg, Alexandra M; Ebeling, Marcus; Ek, Stina; Meyer, Anna; Ding, Mozhu; Talbäck, Mats; Modig, Karin
Abstract: Background: Aging is the primary risk factor for frailty, which is defined as an inability to respond to acute or chronic stressors. Individuals are living longer with greater multimorbidity, but there is a paucity of evidence examining frailty across birth cohorts and ages. Methods: We investigated frailty prevalence and its association with mortality at ages 75, 85, and 95 in the 1895–1945 birth cohorts in Sweden with data from population registries. Frailty was assessed with the Hospital Frailty Risk Score (HFRS). Results: We observed that frailty increased with increasing age and that it has become more common in more recent birth cohorts. At age 75, the percent frail in the Total Population Register increased from 1.1% to 4.6% from birth cohorts 1915–1945, corresponding to calendar years 1990–2020. At age 85, the percentage of frail increased from 3.5% to 11.5% from birth cohorts 1905–1935, and at age 95 from birth cohorts 1895–1925, from 4.7% to 18.7%. Our results show that the increase was primarily driven by an increase in the distribution of individuals with scores in the highest quartile of HFRS, while the bottom 3 quartiles remained relatively stable across birth cohorts. Women accounted for a greater distribution of the overall population and frail population, though these disparities decreased over time. Despite increasing levels of frailty, the relationship between frailty and mortality did not change over time, nor did it differ by sex. Conclusion: Increased frailty with improved survival points to a chronic condition that could be intervened upon.